DIALOG IDENTITAS: INTEGRASI TRADISI KEAGAMAAN LOKAL DI TENGAH ARUS BUDAYA GLOBAL - Aslan, Aslan; Dea Tara Ningtyas (CV. Adiba Aisha Amira, 2025)
The dialogue on identity related to the integration of local religious traditions into the global cultural mainstream highlights the challenges and opportunities faced by local traditions amid cultural homogenisation. Local religious traditions, as key elements of community identity, demonstrate their ability to adapt and retain their meaning when confronted with global cultural influences. This integration process does not always mean conflict, but can create synergies that enrich both sides. Dynamic dialogue allows local traditions to contribute to global culture while utilising modern elements to strengthen their appeal. To maintain the balance and relevance of local traditions, the involvement of various stakeholders through inclusive dialogue is crucial for local religious traditions to survive and thrive in today's global cultural landscape.